The size of sites containing SR proteins in human nuclei. Problems associated with characterizing small structures by immunogold labeling. - Iborra, F; Cook, P (1998)
Some SR proteins are associated with eukaryotic transcripts as they move from synthetic sites (transcription "factories"), through downstream sites, to nuclear pores. Downstream sites can also be isolated as large nuclear ribonucleoprotein particles of approximately 200 S (diameter approximately 50 nm). In ultrathin sections of HeLa nuclei, indirect immunogold labeling with a specific antibody gives many small clusters of approximately 10 gold particles (diameter 50-80 nm). We gauged errors in estimating the diameter of underlying structures marked by immunogold probes (lengths approximately 20 nm). We examined systematically how probe dimensions affected cluster diameter. Probes contained one to three immunoglobulin molecules, sometimes a protein A molecule, and a gold particle of 5-15 nm. We found that (a) immunolabeling particles were tightly packed, (b) reducing particle size by 5 nm reduced cluster diameter by 10 nm, (c) reducing the number of immunoglobulins in the immunolabeling sandwich from three to two reduced cluster diameter by approximately 4 nm, (d) replacing the last immunoglobulin in a sandwich with protein A increased diameter by approximately 7 nm and led to a peripheral concentration of particles, and (e) increasing the number of layers in the sandwich increased sensitivity. Assuming that underlying structures had diameters of 50 nm, we find that errors ranged from -20% to +50%.